The mechanism of colon tissue damage mediated by HIF-1α/NF-κB/STAT1 in high-altitude environment - Cheng, Junfei; Sun, Yuemei; He, Jiaxin; Wang, Zihan; Li, Wenbin; Wang, Rong (Frontiers in Physiology, 2022)
The high altitude environment will damage the intestinal mucosal barrier, leading to a high incidence of intestinal diseases, and seriously affect the working ability of people at high altitude. However, how high altitude induces intestinal mucosal barrier injury has not been well defined. The purpose of this study was to investigate the mechanism of colonic tissue injury induced by the influence of high altitude environment on the colonic microenvironment. Forty-eight SPF C57BL/6J mice were randomly divided into 4 groups,control group and the other three groups were high altitude exposure group (Yushu, Qinghai; 4,010 m;12 h,24 h,48 h). First, HE staining was used to observe the effect of high altitude environment on colon histomorphology of mice. The protein expression levels of Claudin-1, Occludin and ZO-1 were analyzed by molecular biological methods. This altitude did cause inflammatory damage to colon tissue. Intestinal hypoxia was measured with pipermonidazole (PMDZ) hypoxic probe. Interestingly, we observed a decrease in the concentration of oxygen in the microenvironment in the colonic lumen. We sought to explore the mechanism of colonic mucosal barrier damage at different times entering high altitude. The expression levels of hypoxia-inducible factors HIF-1α，STAT1，NF-κB and inflammatory factors IFN-γ, TNF-α and IL-6 were significantly increased. This work highlights that the high altitude environment leads to a reduction in the concentration of oxygen in the microenvironment of the colonic lumen, which disrupts the colonic mucosal barrier and ultimately induces and exacerbates intestinal injury.